Spiritual needs of patients with cancer in palliative care: An integrative review - Mesquita, Ana Cláudia [UNESP]; Chaves, Érika De Cássia Lopes; Barros, Guilherme Antônio Moreira De [UNESP] (Wolters Kluwer, 2017)
Purpose of review The experience of a life crisis, such as the experience of end-of-life terminality whenever facing cancer can make the spiritual needs of patients clear. The goal of this revision was to synthesize the existing evidence regarding the spiritual needs of patients with cancer in palliative care. Recent findings An integrated revision of the literature was conducted regarding the database sources from PubMed, CINAHL, EMBASE, LILACS and Scopus, without publishing year restrictions. There were 16 primary studies included. A total of 1469 patients have been evaluated, whereas eight groups of spiritual needs have been identified: finding the meaning and purpose of life; finding the meaning in experiencing the disease; being connected to other people, God and nature; having access to religious/spiritual practices; physical, psychological, social and spiritual wellbeing; talking about death and the experience of dying; making the best out of their time; being independent and being treated like a normal person. Summary It is essential to pay attention to patients' spiritual dimensions regarding palliative care. Therefore, patients' spiritual needs must be identified and remedied or mitigated. It is necessary to develop studies that find specific strategies and interventions for the treatment of these needs.
Keywords: neoplasms; palliative care; spiritual care